2015
DOI: 10.1038/jhh.2015.98
|View full text |Cite
|
Sign up to set email alerts
|

ARMC5 mutation analysis in patients with primary aldosteronism and bilateral adrenal lesions

Abstract: Idiopathic hyperaldosteronism (IHA) due to bilateral adrenal hyperplasia is the most common subtype of primary aldosteronism (PA). The pathogenesis of IHA is still unknown, but the bilateral disease suggests a potential predisposing genetic alteration. Heterozygous germline mutations of armadillo repeat containing 5 (ARMC5) have been shown to be associated with hypercortisolism due to sporadic primary bilateral macronodular adrenal hyperplasia and are also observed in African-American PA patients. We investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 35 publications
0
24
0
1
Order By: Relevance
“…Page 10 of 31 study failed to confirm this association in patients of European ancestry (42). Similarly, a potential role of ARMC5 in FH-II has been recently ruled out (43).…”
Section: Germline Mutations In Sporadic Pamentioning
confidence: 48%
“…Page 10 of 31 study failed to confirm this association in patients of European ancestry (42). Similarly, a potential role of ARMC5 in FH-II has been recently ruled out (43).…”
Section: Germline Mutations In Sporadic Pamentioning
confidence: 48%
“…Malignant transformation has been reported in incidentally found non-functioning adrenal adenomas [11], and several mitogenic factors are known to control adrenal growth and aldosterone secretion in unilateral/bilateral aldosteronism [12]. Our CT data showed that adrenal mass enlargement in no case exceeded 3 cm of diameter or was associated with signs of malignant transformation, suggesting that mass increase was casual and not a marker of malignancy.…”
Section: Resultsmentioning
confidence: 72%
“…Furthermore, overexpression of mutant ARMC5 was found to downregulate CYP11B2 expression. Recently, Mulatero and coworkers also reported ARMC5 mutations in Caucasian patients (Mulatero et al 2016). They identified 18 variants of ARMC5.…”
Section: Armc5mentioning
confidence: 97%